Utilising feed effectors and automated feeders for semi‐intensive pacific white shrimp (Litopenaeus vannamei) production. Issue 6 (9th November 2022) - Walsh, Samuel; Nguyen, Khanh; Strebel, Leila; Rhodes, Melanie; Davis, D. Allen
Abstract: Feed effectors have been suggested to improve the efficiency of plant‐based shrimp diets by increasing attractability and palatability. This research trial aimed to expand upon previous Pacific white shrimp ( Litopenaeus vannamei ) research involving plant‐based diets, feed effectors and passive acoustic monitoring (PAM) in a laboratory setting by conducting a feed trial in outdoor semi‐intensive ponds stocked at 30 shrimp/m 2 . A 13‐week trial was conducted in sixteen 0.1‐ha ponds equipped with PAM‐integrated feeders, which allowed for demand‐style feeding. Four soy‐optimised diets, consisting of an 'all‐plant' basal diet (AP) and three diets with an attractant (2% krill meal (KM), 2% squid meal (SM), 4% fish hydrolysate (FH)), were fed to the shrimp for a period of 74–75 days. Significantly more ( p  = 0.0131) of the FH diet was fed to the respective ponds than the KM and AP diets, suggesting that the addition of FH to soy‐optimised diets increases the intensity of the feed response in shrimp cultured in semi‐intensive ponds. The same diets offered in predetermined amounts to shrimp in an outdoor, recirculating green water system resulted in no significant differences ( p  > 0.05) between treatment means for final weight or weekly growth rate. However, there was a significant difference ( p  = 0.021) in survival between the AP treatment (85.83%) and the FH treatment (95.83%), which led to the final biomass ( p  = 0.004) and FCR ( p  < 0.0001) of the AP treatment being significantly different from all other treatments. The reduced response observed in the AP treatment suggests that the addition of attractants may improve the performance of plant‐based diets in RAS. Abstract :